EFEKTIVITAS TERAPI AKTIVITAS KELOMPOK STIMULASI PERSEPSI TERHADAP KEMAMPUAN PASIEN DALAM MENGENDALIKAN HALUSINASI MENGGUNAKAN PENDEKATAN HEALTH BELIEF MODEL (HBM) - Firmawati Firmawati; Sabirin B. Syukur (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The purpose of this research is to know the effectiveness of therapy activity of perce ptual stimulation group on the patient's ability to control hallucinations using Health Belief Model (HBM) approach at RSUD Tombulilato Bone Raya Sub-district, Bone Bolango District. The research design used is Nonequivalent Control Group Design. The sample in this study of 11 people for the control group and 11 people for the intervention group. The results showed that there was a difference of therapy of perceptual stimulation group activity on the patient's ability to control hallucinations using Health Belief Model (HBM) approach at Tombulilato District Hospital Bone Raya District Bone Bolango P value = 0,002 (P <0,005)